Geometry and Segmentation of the Philippine Fault in Surigao Strait - Marfito, Bryan J.; Llamas, Deo Carlo E.; Aurelio, Mario A. (Frontiers in Earth Science, 2022)
On 10 February 2017, a MS 6.7 earthquake, whose epicenter was located in Surigao Strait, struck the province of Surigao del Norte, causing numerous geologic impacts and damages to infrastructure. Field investigation conducted immediately after the earthquake revealed an NNW-SSE striking surface rupture that extends 4.1 km inland. The remaining 20 km of the surface rupture was hypothesized to be generated by the Philippine Fault in Surigao Strait based on the computed magnitude-surface rupture length empirical relationship. We investigated the geometry of the fault in Surigao Strait by identifying morphotectonic features and geologic structures using offshore geophysical data that includes multi-beam bathymetry, sub-bottom profiles, and seismic reflection profiles. We interpreted several fault-related features such as pull-apart basin, offset channels, linear valleys, and folds, and identified four fault segments which are named Maka-andog Strand, Surigao-Sanghid Strand, West Sanghid Strand, and Panaon Strand. Based on fault length, these segments are capable of generating MW 6.4 to 6.9 earthquakes. We have determined that surface rupture most probably extends along the entire length of the Surigao-Saghid Strand that generated the 2017 MS6.7 earthquake. The identified morphotectonic features, presence of strike-slip with significant normal displacement in offshore geophysical imaging data, and focal mechanism all suggest that Surigao Strait is dominated by transtensional deformation which supports the interpretations by previous authors.